Hard hit [videorecording (DVD)] - Chi, Ch'ang-uk, 1987-; Cho, U-jin, 1979- (MPI Home Video, 2022)
VIP Bank Manager Sung-Gyu drives his children to school one morning. Along the way, a phone rings from the glove box. It's an anonymous caller claiming there's a bomb under Sung-Gyu's seat and if anyone exits the car, it will explode unless Sung-Gyu pays a ransom. What feels like a prank quickly turns into an edge-of-your-seat thriller. Sung-Gyu must ensure the safety of his children, find enough money to pay the ransom, and evade the police, all while trying to figure out what he did in his past to deserve this.